Model for the prediction of noise generated by fixed sources [Modelo para la predicción del ruido proveniente de fuentes fijas] (2019)
Objective: This article proposes a prediction model applicable to the propagation of noise generated by fixed sources as the result of the analysis of the phenomena related to the generation and propagation of sound levels and the subsequent correlation between the estimated levels and the data recorded in the field. Materials and methods: An experimental program was designed that included the measurement of sound pressure levels with a sound level meter in free field conditions for different weather conditions and distances from the noise emission source for comparison with the levels estimated by ISO 9613 Part 2. A statistical analysis of the data recorded in the field was performed to observe their dependence on the meteorological variables recorded during the measurements. Results and discussion: The standard error for the proposed prediction method is 11.4 dB(A), and the absolute average error is 9.1 dB(A). The correlation coefficient of the proposed model is 0.87. A statistically significant relationship exists between the variables at the 95.0% confidence level. Conclusion: A propagation model that presented a better fit than the method of ISO 9613 Part 2 and a higher correlation coefficient was obtained. © 2019, Pontificia Universidad Javeriana. All rights reserved.